Development of STEM-Based Interactive Learning Multimedia Assisted by Articulate Storyline 3 Oriented to Students' Critical Thinking Skills on Chemical Bonding Material - Misbah Chuddin Nur; Zurweni Zurweni; Firdiawan Ekaputra (Departement of Mathematics Education, 2024)
The government is trying to improve the quality of education by updating the curriculum and technology. Critical thinking means understanding what needs to be understood and planning it. To learn chemistry, students need a good understanding. This is especially true for chemical bonds, which are difficult topics and require a strong understanding of concepts. Because it combines four main areas—science, technology, engineering, and mathematics—STEM helps learningThe purpose of this study was to determine how effective STEM-based interactive media with the help of Articulate Storyline 3 improves students' ability to think critically about chemical bonding material. Interactive media can affect students' ability to think critically, according to research findings. Previous studies have proven this. The study improved students' critical thinking skills in ways such as educating them, focusing questions, analyzing arguments, and deciding on actions. Interactive STEM-based media is very important to improve students' critical thinking skills during the learning process. Therefore, this interactive media has the potential to improve students' critical thinking skills.